HPLC-DAD-MS3 fingerprints of phenolics of selected Polygonum taxa and their chemometric analysis. (April 2023) - Pawłowska, Karolina A.; Kryżman, Maria; Zidorn, Christian; Pagitz, Konrad; Popowski, Dominik; Granica, Sebastian
Abstract: Many Polygonaceae taxa such as Bistorta officinalis, Persicaria amphibia, Persicaria hydropiper, Persicaria lapathifolia, Persicaria maculosa, Persicaria mitis, Polygonum aviculare occur naturally in the entire territory of Poland and are also common in other European countries. Many of these species are also utilised as medicinal plants. In this manuscript we establish the phytochemical profiles of selected taxa from the Polygonaceae focusing on phenolics. Additionally, we try to find chemophenetic markers for the species investigated. Compounds were detected and characterised based on HPLC-DAD-MS data, quantified, and furtherly analysed using multivariate analyses. Chemophenetic markers were identified also considering previous literature. Graphical abstract: Image 1 Highlights: HPLC-DAD-MS 3 analysis of phenolics was performed 128 samples of species from three genera were analysed Multivariate analysis of quantitative results was done Chemophenetic markers were proposed